Zebrafish Recoverin Isoforms Display Differences in Calcium Switch Mechanisms - Dana Elbers; Alexander Scholten; Karl-Wilhelm Koch (Frontiers in Molecular Neuroscience, 2018)
Primary steps in vertebrate vision occur in rod and cone cells of the retina and require precise molecular switches in excitation, recovery, and adaptation. In particular, recovery of the photoresponse and light adaptation processes are under control of neuronal Ca2+ sensor (NCS) proteins. Among them, the Ca2+ sensor recoverin undergoes a pronounced Ca2+-dependent conformational change, a prototypical so-called Ca2+-myristoyl switch, which allows selective targeting of G protein-coupled receptor kinase. Zebrafish (Danio rerio) has gained attention as a model organism in vision research. It expresses four different recoverin isoforms (zRec1a, zRec1b, zRec2a, and zRec2b) that are orthologs to the one known mammalian variant. The expression pattern of the four isoforms cover both rod and cone cells, but the differential distribution in cones points to versatile functions of recoverin in these cell types. Initial functional studies on zebrafish larvae indicate different Ca2+-sensitive working modes for zebrafish recoverins, but experimental evidence is lacking so far. The aims of the present study are (1) to measure specific Ca2+-sensing properties of the different recoverin isoforms, (2) to ask whether switch mechanisms triggered by Ca2+ resemble that one observed with mammalian recoverin, and (3) to investigate a possible impact of an attached myristoyl moiety. For addressing these questions, we employ fluorescence spectroscopy, surface plasmon resonance (SPR), dynamic light scattering, and equilibrium centrifugation. Exposure of hydrophobic amino acids, due to the myristoyl switch, differed among isoforms and depended also on the myristoylation state of the particular recoverin. Ca2+-induced rearrangement of the protein-water shell was for all variants less pronounced than for the bovine ortholog indicating either a modified Ca2+-myristoyl switch or no switch. Our results have implications for a step-by-step response of recoverin isoforms to changing intracellular Ca2+ during illumination.